2015
DOI: 10.1371/journal.pone.0139375
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of Sheep at 45 and 60 Days of Gestation with Schmallenberg Virus Readily Led to Placental Colonization without Causing Congenital Malformations

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…The control samples were defined and tested in preliminary experiments. The positive control sample consisted of pooled sera collected at 10, 11 and 14 dpi from one ewe inoculated with the same inoculum in a different experiment [ 25 ]. The negative control sample consisted of pooled sera collected from ewes in 2005.…”
Section: Methodsmentioning
confidence: 99%
“…The control samples were defined and tested in preliminary experiments. The positive control sample consisted of pooled sera collected at 10, 11 and 14 dpi from one ewe inoculated with the same inoculum in a different experiment [ 25 ]. The negative control sample consisted of pooled sera collected from ewes in 2005.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on the related Akabane virus estimate the vulnerable period to be between days 28 and 56 of pregnancy; however, a recent study demonstrated high placental colonisation of SBV when infected at days 45 or 60 of gestation, but a lack of subsequent abortions and malformations observed in the lambs (EFSA 2012, Martinelle and others 2015). Fetal or neonate malformations typically present as arthrogryposis, scoliosis, kyphosis, severe torticollis, brachygnathia and hypoplasia of the central nervous system (Doceul and others 2013).…”
mentioning
confidence: 99%
“…SBV infections of adult ruminants are generally asymptomatic; however, if infection of a naive pregnant animal coincides with the vulnerable period of gestation, transmission across the placenta can result in abortions, stillbirths and fetal malformations (Beer and others 2013, Doceul and others 2013). Studies on the related Akabane virus estimate the vulnerable period to be between days 28 and 56 of pregnancy; however, a recent study demonstrated high placental colonisation of SBV when infected at days 45 or 60 of gestation, but a lack of subsequent abortions and malformations observed in the lambs (EFSA 2012, Martinelle and others 2015). Fetal or neonate malformations typically present as arthrogryposis, scoliosis, kyphosis, severe torticollis, brachygnathia and hypoplasia of the central nervous system (Doceul and others 2013).…”
mentioning
confidence: 99%
“…The clinical signs of disease in adult cows are quite mild and include fever, a drop in milk yield, and diarrhea with peak viremia 4-7 d post-infection [112]. SBV can both persist in and cross the placenta to replicate in the fetus itself [113]. Depending on the time of exposure, this may result in abortion or severe congenital malformations causing dystocia and the birth of non-viable calves [114,115].…”
Section: Schmallenberg Virusmentioning
confidence: 99%